2000
DOI: 10.1016/s0893-133x(00)00103-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroids Ameliorate Conditioned Fear Stress An Association with Sigma1 Receptors

Abstract: Mice exhibited a marked suppression of motility (conditioned fear stress) when placed in an environment in which they had previously received an electric footshock. This conditioned fear stress response was dose-dependently attenuated by neurosteroids such as dehydroepiandrosterone sulfate (DHEAS; 25 and 50 mg/kg, s.c.) and pregnenolone sulfate (PREGS; s.c.), and by a putative sigma 1 047; 3 and 6 mg/kg, s.c.). However, progesterone (PROG; s.c.) and allopregnanolone (5 and 20 mg/kg, s.c.) had no effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 45 publications
2
40
0
1
Order By: Relevance
“…Because the BNST is implicated in emotional reactivity more akin to anxiety than stimulus-specific fear , the current results suggest that P may be affecting brain systems involved in anxiety versus stimulus-specific fear. In agreement with this, a recent study reported that neither THP nor P reduced the suppression of motility after the onset of conditioned fear stimulus (Noda et al, 2000).…”
Section: Discussionsupporting
confidence: 71%
“…Because the BNST is implicated in emotional reactivity more akin to anxiety than stimulus-specific fear , the current results suggest that P may be affecting brain systems involved in anxiety versus stimulus-specific fear. In agreement with this, a recent study reported that neither THP nor P reduced the suppression of motility after the onset of conditioned fear stimulus (Noda et al, 2000).…”
Section: Discussionsupporting
confidence: 71%
“…376 In addition, PREGS can attenuate the conditioned fear stress response via ó 1 receptors. 377 Albeit speculative, these findings suggest that PREG and PREGS may have therapeutic potential for improving cognitive deficit observed in schizophrenia.…”
Section: Neurosteroidsmentioning
confidence: 98%
“…The neuroactive steroid/s 1 receptor interaction was first demonstrated using binding studies (Su et al 1988;Yamada et al 1994;Maurice et al 1996a), then reported in physiological (Monnet et al 1995;Debonnel et al 1996) and behavioral studies (Maurice et al 1997Reddy et al 1998;Urani et al 1998;Noda et al 2000). In particular, progesterone acts as a potent s 1 receptor antagonist, and physiological variations in the central levels of the steroid directly affect the behavioral efficacy of s 1 receptor agonists Urani et al 2001).…”
Section: Introductionmentioning
confidence: 99%